Pacta Sunt Servanda: Legal Dynamics in Indonesian Context - Cahyo, Yoga Tri; Kurnianingsih, Marisa (Universitas Islam Negeri Walisongo Semarang, 2023)
This article discusses the role of the Pacta Sunt Servanda principle in loan agreements, particularly in the context of a court decision related to the breach of contract by PT BPR Suryamas Surakarta. The principle asserts that an agreement is binding as law to the parties involved and is utilized by judges as a consideration in court. The article aims to analyze the correlation of this principle with the judge's considerations in the context of breach of contract and evaluate the judge's perspective from the standpoint of legal utility. The research employs a normative juridical method through a literature review, using secondary data such as legal regulations and relevant literature. The results indicate that the Pacta Sunt Servanda principle plays a crucial role as a basis for judicial consideration, evident in the court decision that punishes the defendants according to the agreed-upon contract. While legal certainty predominates, the happiness of the parties involved, and the public is also a consideration for the judge. This decision, though emphasizing legal certainty, essentially contributes to the happiness of all parties involved and the community. Artikel ini mendiskusikan peran Asas Pacta Sunt Servanda dalam perjanjian pinjam meminjam, terutama dalam konteks putusan hakim terkait wanprestasi PT BPR Suryamas Surakarta. Asas ini menegaskan bahwa perjanjian berlaku sebagai undang-undang bagi pihak yang membuatnya, dan digunakan oleh hakim sebagai pertimbangan dalam pengadilan. Artikel bertujuan menganalisis korelasi asas tersebut dengan pertimbangan hakim dalam konteks wanprestasi, serta mengevaluasi pertimbangan hakim dari perspektif kemanfaatan hukum. Metode yang digunakan adalah yuridis normatif melalui studi kepustakaan, dengan data sekunder berupa peraturan perundang-undangan dan literatur terkait. Hasilnya menunjukkan bahwa Asas Pacta Sunt Servanda memiliki peranan penting sebagai dasar pertimbangan hakim, tergambar dalam amar putusan yang menghukum tergugat sesuai perjanjian. Meskipun aspek kepastian hukum mendominasi, kebahagiaan pihak terlibat dan masyarakat secara umum juga menjadi pertimbangan hakim. Putusan ini, meskipun lebih menonjolkan kepastian hukum, pada intinya menciptakan kebahagiaan bagi semua pihak terlibat dan masyarakat.